Beyond Words: Classifying Critiques of Linguistic Exegesis in Classical Tafsir - Sahroni, Roni; Nasehudin, Muhamad; Ulinnuha, Muhammad (Jurnal Iman dan Spiritualitas, 2026)
This article examines a critical study of linguistic exegesis. Linguistic interpretation constitutes one of the principal approaches in Qur’anic exegesis. However, in practice, this approach has at times produced interpretations that deviate from the rules of the Arabic language, the contextual meaning of the verses, and established methodologies of Qur’anic interpretation. In modern Qur’anic studies, such deviations are often classified as part of al-dakhīl fī al-tafsīr. Therefore, criticism of linguistic exegesis should not be viewed as a rejection of language itself, but rather as an effort to preserve the objectivity of interpreting divine revelation. This article aims to classify the forms of criticism directed at linguistic interpretation and to present their examples in classical exegetical works. This study employs a qualitative method with a library research approach, examining works of Qur’anic exegesis and Qur’anic sciences. The findings indicate that criticism of linguistic exegesis can be categorized into three main forms: first, criticism of lexical interpretation; second, criticism of the application of grammatical rules; and third, criticism of the use of Qur’anic readings (qira’at) within the linguistic approach to Qur’anic interpretation.